A vision for actionable science in a pandemic (2020)
How were you involved with COVID-19 response? C.B.: When there were 17 confirmed COVID-19 cases in Germany in late February, we started preparing a weekly COVID19 Snapshot Monitoring (COSMO)1. COSMO went online one week later when we had 159 cases. Reducing transmissions of COVID-19 requires large-scale behavioural change. Knowledge about the determinants of behaviour is a crucial lever to instigate and maintain behavioural change2. Thus, we assessed people’s risk perceptions, trust in government and science, knowledge, acceptance of measures, psychological strain and mental health aspects of the outbreak. Currently, we have surveyed almost 16,000 participants, approximately 1000 per week. The results are published on a website (www.corona-monitor.de3) and the government and other relevant stakeholders receive additional policy briefs. We cooperated with the World Health Organization’s Regional Office for Europe who adapted the study protocol4, and approximately 40 countries intended to employ similar study protocols to deliver evidence about the psychological aspects of this crisis. In Germany, this assessment allowed identifying groups with special needs, such as families with children under 14 years of age, and provided feedback about the uptake of newly recommended behaviours, such as mask wearing.